If cosec θ + cot θ = K, 0° < θ < 90°, then find \(\frac{(K -1)^2 - 2}{(K+1)^2 - 2K}\) ? |
cos θ - sin θ sin θ - cos θ sin θ + cos θ sec θ cosec θ |
cos θ - sin θ |
Let K = 3 so triplets = (3, 4, 5) Here, ⇒ cosec θ + cot θ ⇒ \(\frac{5}{3}\) + \(\frac{4}{3}\) ⇒ \(\frac{9}{3}\) = 3 Hence, Put K = 3 in \(\frac{(K\;-\;1)^2\;-\;2}{(K\;+\;1)^2 -\;2K}\) ⇒ \(\frac{(3\;-\;1)^2\;-\;2}{(3\;+\;1)^2\;-\;2(3)}\) = \(\frac{4\;-\;2}{16\;-\;6}\) = \(\frac{2}{10}\) = \(\frac{1}{5}\) Put value in option cos θ - sin θ = \(\frac{4}{5}\) - \(\frac{3}{5}\) = \(\frac{1}{5}\) |